Ugarit at Seventy-Five : [proceedings of the Symposium "Ugarit at Seventy-Five" held at Trinity International University, Deerfield, Illinois, February 18-20, 2005 under the auspices of the Middle Western Branch of the American Oriental Society and the Mid-West Region of the Society of the Biblical Literature] - Younger, K. Lawson (Eisenbrauns, 2007)
"Seventy-five years have passed since the beginnings of the study of Ugarit and the Ugaritic language, and the impact of this discovery is still being felt. The first five essays in this volume deal with the Ugaritic texts, while the last three deal with archaeological or historical issues."--Jacket.